Case report: laringoplasty followed by ventriculectomy in hemiplegic equine - Ramos, Fernando Silva; Fonseca, Lysandra Martineli (Revista Coleta Científica, 2019)
Among the frequent affections that affect the respiratory system of racehorses, laryngeal hemiplegia is considered the main of these pathologies, which is characterized by the collapse of the arytenoid cartilage, resulting from a progressive distal degenerative axonopathy of the recurrent laryngeal nerves, the left being more commonly affected, with breathing noises during exercise, dyspnea and loss of athletic performance. The present work reports a case of surgical correction of laryngeal hemiplegia in a horse racing English horse, the animal presented progressive loss of performance in running, dyspnea and exacerbation of respiratory sounds, endoscopy of the upper airways was performed as a method confirmatory diagnosis of the disease and the therapeutic approach was based on a laryngoplasty using the Tie Back technique followed by a Ventriculectomy maneuver. After the postoperative period, the animal showed complete remission of the condition, returning to its normal sports performance.